2004
DOI: 10.1097/01.ccm.0000109449.99160.81
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal permeability of inner and outer mitochondrial membranes contributes independently to mitochondrial dysfunction in the liver during acute endotoxemia*

Abstract: These studies confirm that liver mitochondria are early targets of injury during endotoxemia and that inner and outer mitochondrial membrane damage occurs through different mechanisms. Inner mitochondrial membrane damage appears to relate to the mitochondrial permeability transition, whereas outer mitochondrial membrane damage can occur independent of the mitochondrial permeability transition. Preliminary evidence suggests that Bax may participate in lipopolysaccharide-induced outer mitochondrial membrane dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 51 publications
2
61
1
1
Order By: Relevance
“…Irrespective of the source of these increased free iron levels, it was important to determine whether these increased iron levels can exert deleterious effects on cellular function. As mitochondria are considered an important target for pathological effects of LPS, 20,21,24,25,38 we investigated mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrespective of the source of these increased free iron levels, it was important to determine whether these increased iron levels can exert deleterious effects on cellular function. As mitochondria are considered an important target for pathological effects of LPS, 20,21,24,25,38 we investigated mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] In contrast, intravenous injection/infusion of endotoxin mostly affects mitochondrial function by decreasing state 3 respiration and ATP synthesis at least in the late phase of endotoxic shock. [19][20][21][22] However, intravenous infusion of E. coli has been shown both to improve and to decrease respiration in state 3. 23 Another important observation was that mitochondrial respiration often increases in the early phase of acute critical illness, including septic/endotoxic shock, but consistently falls during the late phase of illness.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, during acute experimental ischemia, inflammation, and/or oxidative stress, various studies have reported impaired (Crouser et al, 2004;Gellerich et al, 1999), unchanged (Mela-Riker et al, 1992Taylor et al, 1995), or improved (Taylor et al, 1998;Lu et al, 2003) mitochondrial function. Such discrepancies have many causes, such as type of cell injury, duration and severity of injury, the cell type and function, and the experimental situation.…”
Section: Mitochondrial Biogenesis and Mitochondrial Turnovermentioning
confidence: 99%
“…8-, 12-, 15-HETE, and the downstream metabolites have systemic anti-and prothrombotic activities (33)(34)(35). They are also involved in pulmonary vascular smooth muscle remodeling and apoptosis (36)(37)(38), but complete understanding of the physiological roles of these metabolites cascades leading to the production of leukotoxins including HODEs and EpOMEs (31). Our results show that LPS treatment increased the systemic levels of these metabolites while levels after treatment with either simvastatin or dLGG were comparable to those of the vehicle control.…”
Section: Simvastatin and Dlgg Lower Production Of Proinflammatory Lipmentioning
confidence: 99%